Physiological concentrations of soluble uric acid are chondroprotective and anti-inflammatory - Jenn-Haung Lai (Nature Portfolio, 2017)
Abstract High uric acid levels are a risk factor for cardiovascular disorders and gout; however, the role of physiological concentrations of soluble uric acid (sUA) is poorly understood. This study aimed to clarify the effects of sUA in joint inflammation. Both cell cultures of primary porcine chondrocytes and mice with collagen-induced arthritis (CIA) were examined. We showed that sUA inhibited TNF-α- and interleukin (IL)-1β–induced inducible nitric oxide synthase, cyclooxygenase-2 and matrix metalloproteinase (MMP)-13 expression. Examination of the mRNA expression of several MMPs and aggrecanases confirmed that sUA exerts chondroprotective effects by inhibiting the activity of many chondro-destructive enzymes. These effects attenuated collagen II loss in chondrocytes and reduced proteoglycan degradation in cartilage explants. These results were reproduced in chondrocytes cultured in three-dimensional (3-D) alginate beads. Molecular studies revealed that sUA inhibited the ERK/AP-1 signalling pathway, but not the IκBα-NF-κB signalling pathway. Increases in plasma uric acid levels facilitated by the provision of oxonic acid, a uricase inhibitor, to CIA mice exerted both anti-inflammatory and arthroprotective effects in these animals, as demonstrated by their arthritis severity scores and immunohistochemical analysis results. Our study demonstrated that physiological concentrations of sUA displayed anti-inflammatory and chondroprotective effects both in vitro and in vivo.